A Vehicle Fuel Consumption Model on Reconstructed Roads Based on the Roughness and Its Measurement Method. (21st July 2021) - Liu, Qiang; Xie, Jianguang; Zhang, Zhixiang
Abstract : The fuel consumption model for a vehicle forms a basis and method for evaluating the social benefit of road reconstruction. Based on the theoretical fuel consumption model of vehicles, the influence mechanism of the apparent parameters of the road surface on the fuel consumption of vehicles and their sensitivity was analysed. The baseline state was defined on the basis of the roughness, a parameter with significant influence. In addition, a method for acquiring fuel consumption parameters was proposed to establish a one-parameter relational model for the roughness and fuel consumption of vehicles in the baseline state based on measured data. Moreover, by considering the effects of the friction coefficient, deflection of the road surface, and vehicle speed on the fuel consumption, a modified model for the fuel consumption of vehicles applicable to road reconstruction was established. Finally, a method for measuring the energy-saving benefit of vehicles was proposed based on the characteristics of reconstructed roads. The research provides a basis for evaluating the social benefit acquired from reconstructed roads.